Accumulated Hard-tissue Debris Removal Using Different Ultrasonic Power Settings: A Micro-CT Study - de Moura Pereira, Flávia; Baroudi, Kusai; Walia, Tarun; Padmanabhan, Vivek; da Silva, Emmanuel Joao Nogueira Leal; de Oliveira Lima, Carolina; Vitti, Rafael Pino; Khoury, Rayana Duarte [UNESP]; da Rosa Cardoso, Flávia Goulart [UNESP] (Thieme, 2025)
To evaluate the effectiveness of the Irrisonic Power ultrasonic tip activated at different power settings (10 and 30%) on the removal of accumulated hard-tissue debris (AHTD) from mandibular premolars using micro-computed tomography (micro-CT) analysis.A total of 20 extracted mandibular premolars were pair-matched based on root canal morphology using micro-CT imaging. All specimens were prepared with Reciproc R25 and randomly assigned to two experimental groups (n  =  10) according to the power setting used during final irrigation: Irrisonic Power 10% or Irrisonic Power 30%. Supplementary irrigation was performed with sodium hypochlorite and EDTA. AHTD was quantified pre- and post-irrigation using standardized micro-CT analysis and ImageJ software.Data were statistically analyzed using the Mann-Whitney test (α  =  0.05).Both protocols significantly reduced AHTD after supplementary irrigation. The Irrisonic Power 30% group exhibited lower residual debris (0.16  ±   0.13%) than the Irrisonic Power 10% group (0.90  ±   1.16%), with a statistically significant difference (p <  0.05).Supplementary irrigation with the Irrisonic ultrasonic tip at 30% power was more effective in removing AHTD than the 10% power setting.